1977
DOI: 10.1021/bi00644a004
|View full text |Cite
|
Sign up to set email alerts
|

Lipid binding by fragments of apolipoprotein C-III-1 obtained by thrombin cleavage

Abstract: We have used thrombin to cleave apolipoprotein C-III-1 into two fragments constituting residues 1-40 (apoLP-C-III-A) and 41-79 (apoLP-C-III-B). The lipid binding properties of these fragments with dimyristoyl- and 1-palmitoyl-2-oleoylphosphatidylcholines have been determined using circular dichroic and intrinsic tryptophan fluorescence spectroscopy. The peptide-phospholipid mixtures were fractionated by density gradients of cesium chloride. ApoLP-C-III-A showed disordered structure in the absence and presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
22
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 11 publications
3
22
0
Order By: Relevance
“…No secondary structure was induced in the N-terminal fragment when added to DMPC liposomes. In contrast, the ␣-helical content was increased in the C-terminal fragment, indicating lipid binding (60). In that study, only the C-terminal fragment was capable of inhibiting LPL activity, but the fragment was somewhat less potent when compared with the fulllength protein.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…No secondary structure was induced in the N-terminal fragment when added to DMPC liposomes. In contrast, the ␣-helical content was increased in the C-terminal fragment, indicating lipid binding (60). In that study, only the C-terminal fragment was capable of inhibiting LPL activity, but the fragment was somewhat less potent when compared with the fulllength protein.…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies had shown that cleavage of apoC-III by thrombin generates two fragments (residues 1-40 and 41-78) (60,61). No secondary structure was induced in the N-terminal fragment when added to DMPC liposomes.…”
Section: Discussionmentioning
confidence: 88%
“…Structure predictions have indicated that two amphipathic helices are likely to be formed (1,27). There is no consensus about which regions are most important for attachment to lipids (27)(28)(29). The structurally related apoCII is known to interact with LPL and activate this enzyme via the C-terminal helix (30), most likely in a dynamic fashion (23).…”
mentioning
confidence: 99%
“…A fundamental property is that the protein can bind rapidly and reversibly to lipoproteins. Sparrow et al [40] showed that the ability to bind to lipid resides in the C-terminal half of human apo CIII. Later Sparrow and Gotto [41] reported that fragment 49-80 bound to lipid, but that fragment 56-80 did not (residue numbers according to Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Based on theoretical and physical studies it is assumed that residues 41 -67 form an amphipathic helix on interaction with lipid [39]. In support of this, Sparrow et al [40] reported that when apo CIII was cleaved with thrombin, fragment 41 -79, but not fragment 1-40 bound to lipid. Furthermore, Sparrow and Gotto [41] reported that the synthetic fragments 41 -79 and 48 -79 bound to phospholipids, while the shorter fragments 55-79 and 61 -79 did not.…”
mentioning
confidence: 99%